Automação do processo de pesagem dinâmica para classificação de cortes de Frango - Lazzaretti, Willian (2019)
The process of separating, sorting and weighing chicken cuts in slaughterhouses is carried out through conveyor belts coupled with a dynamic weighing system, in order to meet the demands of the consumer market, especially the external market. This work deals with the automation of this process in order to guarantee greater reliability, safety and final quality in the process of separation of the items in a slaughterhouses line. Its main function is to classify the weighted part by the criterion of weight range, already stipulated previously in the configuration of the machine through a graphical interface. The system consists of modern controllers, drives and sensors, of consolidated brands in the field of automation, available in the market and developed with focus on the automation of industrial processes. The integration of these devices has resulted in a modern and robust system with a maximum weighing capacity of 2000g and error below 2g in 85% of weighings at a speed of 125 pieces per minute. In addition, it enables instant configuration, miscellaneous information visualization and data delivery to the production management system.